2002
DOI: 10.1038/sj.bjc.6600579
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear BAG-1 expression reflects malignant potential in colorectal carcinomas

Abstract: BAG-1 is a recently identified Bcl-2-interacting anti-apoptotic protein. The aim of our study was to investigate the immunohistochemical staining pattern of BAG-1 protein in patients with colorectal cancer and examine associations of BAG-1 expression with various clinicopathological factors and patient survival. Tumour samples were collected from 86 patients diagnosed with colorectal cancer. There was significant variation in the immunohistochemical staining patterns for BAG-1, including absent staining and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 19 publications
5
18
0
Order By: Relevance
“…32 Interestingly in colon cancer, BAG-1 is overexpressed and nuclear BAG-1 expression is associated with poor survival. 7,24 In the current study we have shown that the maintenance of high levels of nuclear BAG-1 expression, through either BAG-1L or nuclear localised BAG-1S, caused resistance to γ -radiation induced apoptosis. This is the first study to demonstrate that nuclear BAG-1 inhibits the induction of apoptosis in colorectal adenomaderived cells, and suggests that nuclear localised BAG-1 expression may confer a survival advantage on adenoma cells in vivo, which could be important in the early stages of colorectal carcinogenesis.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…32 Interestingly in colon cancer, BAG-1 is overexpressed and nuclear BAG-1 expression is associated with poor survival. 7,24 In the current study we have shown that the maintenance of high levels of nuclear BAG-1 expression, through either BAG-1L or nuclear localised BAG-1S, caused resistance to γ -radiation induced apoptosis. This is the first study to demonstrate that nuclear BAG-1 inhibits the induction of apoptosis in colorectal adenomaderived cells, and suggests that nuclear localised BAG-1 expression may confer a survival advantage on adenoma cells in vivo, which could be important in the early stages of colorectal carcinogenesis.…”
Section: Discussionmentioning
confidence: 95%
“…Recently it has been reported that nuclear BAG-1 expression reflects poorer prognosis and is potentially a useful predictive factor for distant metastasis in patients suffering from colorectal cancer. 24 This suggests that nuclear BAG-1L could be important in the development of colorectal cancer.…”
Section: Introductionmentioning
confidence: 98%
“…The percentage of CRC cases exhibiting nuclear BAG-1 positivity was significantly higher in distant metastasis-positive cases than in distant metastasis-negative cases, overall survival was significantly shorter for patients with tumors exhibiting BAG-1 positive nuclei than those without nuclear BAG-1-staining, and indicated that nuclear BAG-1 expression was the only independent prognostic variable for mortality (Kikuchi et al, 2002).…”
Section: Relationship Between St13 Expression and Survivalmentioning
confidence: 88%
“…Bag-1 almost has no expression in normal tissues, but in the breast, ovarian, oral cavity, bowel malignancy, prostate cancer and glioma has the positive express [1][2][3][4][5][6][7] . Liu et al [8] using fluorescence quantitative polymerase chain reaction (PCR) testing also found the lung cancer patients who have Bag-1 lower expression survived longer than those who have higher expression of expression of Bag-1, so Bag-1 high expression may be related to the poor outcome.…”
Section: Discussionmentioning
confidence: 99%